Islamic Cognitive Restructuring dalam Menangani Konsep Diri Rendah Seorang Siswa Kelas VIII di SMP Khadijah Surabaya - Ramadhoni, Sri Rahmah (Jurusan Bimbingan dan Konseling Islam, 2018)
Teenagers can’t be separated from several conditions that occur in the development period, one of which is the search for identity, in this context students are often involved with various problems. Individual behavior will same with the views of himself. This means that self-concepts both positive and negative, will determine the behavior displayed by individuals. With Islamic Cognitive Restructuring to solve problems, help, and direct clients in solving problems so that the self concept by the counselee can be realized. This study uses a qualitative approach with a type of case study research. The technique in this study uses interview and observation guidelines. The results of this study show that cognitive modification with Islamic Cognitive Restructuring can provide positive changes to the counselee such as being able to identify negative thoughts and rearrange negative thoughts to be realistic. Meanwhile, behavior modification by improving self-appearance can make counselees to understand the usefulness of these modifications in everyday situations.